2010
DOI: 10.1175/2010jpo4378.1
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment on the Nonbreaking Surface-Wave-Induced Vertical Mixing

Abstract: Mixing induced by nonbreaking surface waves was investigated in a wave tank by measuring the thermal destratification rate of the water column. One experiment without waves and four experiments with waves of amplitudes ranging from 1.0 to 1.5 cm and wavelength from 30 to 75 cm were conducted. Water temperature variations at depths from 4 to 12 cm below the surface were measured. In the layer from 4 to 7 cm, the originally dense isothermal lines disperse soon after the waves are generated, whereas the vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 27 publications
2
74
0
4
Order By: Relevance
“…Nevertheless, the turbulent viscosity model is not widely recognized yet, as far as its full and regular justification does not exist. On the other hand, some experimental results in the field of studying the wave-induced turbulence have already appeared [20,32,33] and this fact stimulates our efforts in this field.…”
Section: General Ideas and Objectives Of The Workmentioning
confidence: 94%
“…Nevertheless, the turbulent viscosity model is not widely recognized yet, as far as its full and regular justification does not exist. On the other hand, some experimental results in the field of studying the wave-induced turbulence have already appeared [20,32,33] and this fact stimulates our efforts in this field.…”
Section: General Ideas and Objectives Of The Workmentioning
confidence: 94%
“…Instead, the existence or nonexistence of turbulence was decided by a more subjective criterion, being whether or not the experimenters had judged the dye to have sufficiently dispersed. The weak, intermittent turbulence observed by Babanin and Haus would only be expected to create a visual difference after several hundred periods (see also Dai et al, 2010). Beyá et al (2012) only observed their dye over 5-10 wave periods, so they could not have seen any significant effect visually.…”
Section: Appendix B the Experimental Paper By Beyá Et Al (2012)mentioning
confidence: 95%
“…We note also that the B v model was applied with considerable success in modelling a controlled laboratory experiment for temperature diffusion in a wave tank (Dai et al, 2010).…”
Section: The B V Parameterisation Of Qiao Et Al (2004)mentioning
confidence: 98%
See 1 more Smart Citation
“…The second generation mechanism was considered main at the initial stage of marine subsurface turbulence development [5,12]. Later, semiempirical models, where the wave breaking mechanism was considered main, were proposed [6,10,11]. However, over the last years an issue of wind-generated sea wave turbulence importance became urgent again [9 -11].…”
mentioning
confidence: 99%